A preliminary study of stability in elite and novice 10 meter air pistol shooters - Chadefaux, D.; Valdes-Tamayo, L.; Moreno Flores, R.; Poulet, Y.; Herrera Altamira, G.; Hybois, S.; Coursimault, M.; Sauret, C.; Attali, V.; Thoreux, P. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
Numerous processes are involved in 10 meter air pistol performance such as physiological (Tremayne and Barry 2001), sensorimotor (Cheng et al. 2017), or psychological (Baeck et al. 2012). From a biomechanical point of view, the posture stability has been investigated through the athlete`s center of pressure (CoP) (Ko et al. 2017) as well as the upper-limb motion (Kevin et al. 2003). A high stability, reflected by a low CoP excursion and velocity, has been related to a high performance (Ko et al. 2017). To understand how to maximize the shooter`s stability, several postural features have been discussed. For instance, (Hawkins and Sefton 2011) pointed out that the higher the stance width, the higher the CoP excursion and velocity, and the poorer the shoot performance. Under this framework, a detailed description of the CoP/Posture relationship may be noteworthy to understand shoot performance. For this purpose, although most studies focused on the whole-body CoP, we hypothesize that getting more insight into the CoP evolution under each foot may be valuable to improve performance. The objective of the present study is therefore to compare the CoP under each foot for elite and novice shooters.